e-Banking and Customer Satisfaction in Commercial Banks: A Case of Centenary Bank Main Branch-Mapeera House of Uganda - Nabaasa, Rodgers; Eze, Val Hyginus Udoka; Tukundane, Adonia (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2024)
This study aimed to investigate the correlation between electronic banking (e-banking) and customer satisfaction within Centenary Banks. Employing a cross-sectional survey design, the research involved 85 participants, from whom a sample of 70 was selected. Data collection was facilitated through a self-administered questionnaire. Rigorous data processing and analysis, utilizing relevant statistical software packages, were applied to evaluate the relationships explored in the study. The results demonstrated positive and significant associations between e-banking and customer satisfaction. Moreover, the findings indicated that the model could only account for a 24.4% variance in service quality. In summary, the study affirmed that independent variables such as e-banking, networking, and customer perceptions regarding service value were crucial predictors of service quality in Centenary Bank. Based on the conclusions drawn, the study recommends expanding the investigation to encompass factors not initially included in the model for a more comprehensive understanding of service quality at Centenary Bank. Additionally, it suggests that Centenary Bank's management place significant emphasis on e-banking and networking to enhance overall service delivery. Furthermore, the recommendation extends to conducting a longitudinal study to unveil the evolving nature of the subject. Finally, the model proposed in this study should be applied to explore sectors beyond the financial domain.